Teachers as Change Agents in a Dynamic Society: Challenges and the Prospects - Benebo-Solomon Wilhelmina (International Journal on Integrated Education, 2023)
This paper focuses on teachers as change agents in a dynamic society. It critically examined the concept of a dynamic society, teachers as change agents. The paper argues that teachers are change agents within the classroom, school and the society at large and as such should become role models for the younger generation. This in line with the objectives of primary education as stipulated in the National Policy on Education (2014) one of which is to mold the character and develop sound attitude and morals in the child. However, this responsibility of the teacher is not without difficulties. The paper further highlighted the challenges facing teachers as they seek to become change agent as well as the prospect of teachers as change agents. In conclusion, it was stressed that teachers should strive to be the agents of change within their domain by being role models to the children under their care.